Son of the Laocoön Alonso Berruguete and pagan Antiquity - Arias Martínez, Manuel; Bolaños Atienza, María 1951-; Farinella, Vincenzo 1957-; Morán Sánchez, Carlos Jesús ca. 20./21. Jh; Morán Turina, José Miguel; Mozzati, Tommaso (Secretaría General Técnica, Subdirección General de Documentación y Publicaciones, 2018)
Alonso Berruguete (c. 1489?1561), the first Spanish Renaissance sculptor, spent a fruitful stint in Italy, where he came into contact with Michelangelo, Raphael, and Bramante and was influenced by their enthusiasm for ancient ideals and their attitude to art. Sarcophaguses, ruins and statues fired his imagination, especially the Laocoön: its theatrical pathos, anatomical virtuosity, and bodies dancing in space left an indelible mark on his oeuvre. Upon his return to Castile he felt himself to be a Renaissance man, a new artist willing to defy the old authorities and defend his ingenium. Drawing on this heritage, he produced works steeped in emotion and visual vehemence that reveal an obsessive preference for the sombre and nocturnal brand of Renaissance art: Dionysian as opposed to Apollonian brand, characterised by tormented and exaggerated gestures, expressive frenzy and the terribilità suffered by Laocoön's sons. For Berruguete's pulsating modernity stems from his anticlassical classicism, the importance he attaches to freedom of rhythm and anguish, and an extreme subjectivity that combines the force of the ancient with the freshness of the modern
"Gobierno de España, Ministerio de Cultura y Deporte, CEEH Centro de Estudios Europa Hispánica, with the collaboration of CSA Center for Spain in America"
"First published in Spanish under the title Hijo del Laocoonte. Alonso Berruguete y la Antigüedad pagana by the Ministerio de Educación, Cultura y Deporte, 2017"--Colophon
Includes bibliographical references and index
Keywords: Hagesander -- ca. v50 -- Laokoongruppe; Berruguete, Alonso -- 1486-1561; Antike; Mensch -- Motiv; Plastik; Rezeption; Römisches Reich; Ausstellungskatalog